A novel nonsense mutation in the TRPS1 gene in a case of trichorhinophalangeal syndrome type I - Li-Hsuan Chen; Chung-Chu Ning; Sheau-Chiou Chao (Wolters Kluwer Medknow Publications, 2011)
The trichorhinophalangeal syndromes are rare malformation syndromes with autosomal dominant inheritance. Diagnostic features include distinctive facial dysmorphisms and various skeletal abnormalities. The affected gene, the TRPS1 on 8q24.1, was first identified in 2000 and more than 50 mutations have been found. We present a patient with a novel nonsense mutation in the TRPS1 gene.